Solução numérica de equações diferenciais para precificação de opções - Thomaz, Julio Cezar Alves (2015)
Made available in DSpace on 2015-03-04T18:50:52Z (GMT). No. of bitstreams: 1 dissertacao.pdf: 1038066 bytes, checksum: 0c944d0201d676758ed46389266e18f6 (MD5) Previous issue date: 2005-12-22